2014
DOI: 10.1590/s1516-35982014001000005
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur sources in protein supplements for ruminants

Abstract: -The present study evaluates the efficiency of different sulfur sources for ruminant nutrition. The fiber digestibility and the amino acid profile were analyzed in the duodenal digesta of crossbred steers fed Brachiaria dictyoneura hay. The sources utilized were elemental sulfur (ES70S), elemental sulfur (ES98S); calcium sulfate in hydrated (HCS), CaSO4.2H 2 O, and anhydrous (ACS), CaSO 4 , forms; and ammonium sulfate (AS), (NH 4 ) 2 SO 4 , keeping a nitrogen:sulfur ratio of 11:1. The iso-protein supplements h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Different microorganisms use elemental sulfur as an electron acceptor; therefore, the reduced forms of sulfur (sulfite and sulfide) are a metabolic end product of fermentation from these microorganisms [41]. This could be because the non-protein nitrogen utilization is increased by high levels of sulfur in the rumen fluid, indicating microbial growth [5]. Furthermore, propionic acid increased by 4.6% when diets were supplemented by 2.5% sulfur (p < 0.01).…”
Section: Volatile Fatty Acid (Vfa) Concentration In the Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…Different microorganisms use elemental sulfur as an electron acceptor; therefore, the reduced forms of sulfur (sulfite and sulfide) are a metabolic end product of fermentation from these microorganisms [41]. This could be because the non-protein nitrogen utilization is increased by high levels of sulfur in the rumen fluid, indicating microbial growth [5]. Furthermore, propionic acid increased by 4.6% when diets were supplemented by 2.5% sulfur (p < 0.01).…”
Section: Volatile Fatty Acid (Vfa) Concentration In the Rumenmentioning
confidence: 99%
“…In ruminants, it is dangerous and usually will cause death when an animal receives HCN at a concentration of 1000 ppm (dry matter [DM] basis) [4]. Sulfur can be fed directly in the diet; microbial use of sulfur-containing amino acids synthesis is essential for maximum microbial growth and DM digestibility and can reduce the concentration of HCN [5].…”
Section: Introductionmentioning
confidence: 99%
“… Silva et al (2014) mentioned that sulfur is an important component of sulfur-containing amino acids used by microbes in microbial digestion. We found that sulfur had a positive effect on the Lactobacillus population, which may have partly increased microbial digestion and, consequently, increase feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…The significance positive nitrogen and sulfur retention indicates high correlation between them under the condition of the present experiment. Silva et al (2014) reported that the presence of sulfur in sheep diet affect directly on feed intake because the synthesis of sulfur-containing amino acids (S-AA) is essential for the maximum microbial growth in the rumen and consequently, DM digestibility. They added that, the N/S ratio in the rumen microbial proteins is 14.5:1, and a sulfur deficiency in sheep diet causes low microbial fermentation and reduces the utilization of lactate by the rumen bacteria, resulting in its accumulation.…”
Section: Sulfur Metabolismmentioning
confidence: 99%
“…sulfur thus improves the microbial digestion of cellulose and thus contributes to amino acid synthesis in particular methionine and cysteine. Many species of the rumen bacteria need sulfur which can be obtained by several ways (Silva et al, 2014). Some microorganisms are able to convert inorganic sulfur sources into sulfide and incorporating this compound to the amino acids, while others use organic sulfur only (Durand and Komisarczuk, 1988).…”
Section: Sulfur Metabolismmentioning
confidence: 99%